Public Sociology and Participatory Approaches. Towards a Democratization of Social Research? - Cataldi, Silvia (Qualitative Sociology Review, 2014)
The subject of participation has been gathering increasing interest from the various social disciplines: from politology to psychology, from urban sociology to evaluation, this concept carries a particular fascination and discussing participatory research has now become an absolute must. However, an adequate reflection on methodologies for analyzing research practices and evaluating hypotheses and effects when setting up actual research relationships has not followed on the tail of this new tendency. This paper arises from that need and aims, through discussion of the main debates that have interested science and sociology, to reevaluate a critical approach towards the analysis of the social relationships that are created during a research investigation. This study starts out as a reflection aimed at analyzing the impact that participation, in all its various forms, can have on the way research is carried out. The originality of this article lies in the proposal of a form of participation, and from this, the expression of a hope for the future of social sciences: that we can aspire towards a dialogical model and towards a new cooperative and emancipatory relationship with the public.